2016
DOI: 10.1007/s00192-016-3108-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesh complications and failure rates after transvaginal mesh repair compared with abdominal or laparoscopic sacrocolpopexy and to native tissue repair in treating apical prolapse

Abstract: Reoperation for apical prolapse is more common with TVMR than with sacrocolpopexies and NTR. Incontinence procedures are more likely to fail when performed along with prolapse repair than when performed alone. When mesh is used for repair, mesh revision is highest with TVMR and lowest with ASCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Most studies were of a retrospective design (73.8%). The literature on LSC and RSC shows erosion rates between 0 and 13.3% (range of number of patients included: 12-4,552; range of follow-up 12-72 months) [3,5,. The articles that were included differed in their methods and inclusion criteria.…”
Section: Overview Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Most studies were of a retrospective design (73.8%). The literature on LSC and RSC shows erosion rates between 0 and 13.3% (range of number of patients included: 12-4,552; range of follow-up 12-72 months) [3,5,. The articles that were included differed in their methods and inclusion criteria.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…This is in line with the mesh erosion rate found in our study. Dandolu et al [3] described a large retrospective cohort of patients (N = 4,552, follow-up ≥2 years) with an apical prolapse who underwent LSC. Mesh removal or revision occurred in 52 patients (1.7%).…”
Section: Overview Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, native tissue repair and abdominal approach repair are expected to gain increasing attention for POP management because of the expected decreasing trend of TVM use. For apical prolapse, laparoscopic approaches, such as LLMS, are minimally invasive and have a lower reoperation rate than native tissue repair 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this approach can reduce mesh PPP to a level no greater than after native tissue repair. 5 The prevalence of PPP after retropubic slings is low, so low that it can't be discovered among existing comparative trials that include robust quality of life scoring. Perhaps larger multicentre studies are needed or else these women don't enrol in trials, 6 but they exist, as the large numbers involved in the Shine class action demonstrate.…”
mentioning
confidence: 99%